2018
DOI: 10.1016/j.stemcr.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of CD200 and CD200R1 Distinguishes Stem and Progenitor Cell Populations within Mammary Repopulating Units

Abstract: SummaryAiming to unravel the top of the mammary epithelial cell hierarchy, a subset of the CD49fhighCD24med mammary repopulating units (MRUs) was identified by flow cytometry, expressing high levels of CD200 and its receptor CD200R1. These MRUCD200/CD200R1 repopulated a larger area of de-epithelized mammary fat pads than the rest of the MRUs, termed MRUnot CD200/CD200R1. MRUCD200/CD200R1 maintained a much lower number of divergently defined, highly expressed genes and pathways that support better cell growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…However, both CD200 high CD200R1 high MRUs and CD200 -CD200R1subset of MRUs shared some common stem cell markers. This suggested that CD200 high CD200R1 high MRUs represented stem cells, while CD200 -CD200R1 -MRUs represented common/bipotential progenitors [48]. Some CD200 high CD200R1 high cells did not show mammary regenerative activities and were though to represent more differentiated myoepithelial cells.…”
Section: Mouse Mammary Stem Cells and Progenitorsmentioning
confidence: 99%
“…However, both CD200 high CD200R1 high MRUs and CD200 -CD200R1subset of MRUs shared some common stem cell markers. This suggested that CD200 high CD200R1 high MRUs represented stem cells, while CD200 -CD200R1 -MRUs represented common/bipotential progenitors [48]. Some CD200 high CD200R1 high cells did not show mammary regenerative activities and were though to represent more differentiated myoepithelial cells.…”
Section: Mouse Mammary Stem Cells and Progenitorsmentioning
confidence: 99%
“…The SMART-Seq2 protocol (Picelli et al 2014) was adapted with several modifications, as described below, to generate libraries for bulk RNA-Seq of individual cell lines included in the HNSCC custom pool (see 'Cell line assignment') and for profiling of bronchial primary cells following senescence induction with etoposide ( fig. S4E) (Rauner et al, 2018). Between 100-200 cells were resuspended in lysis buffer containing Triton 0.2% and RNAase inhibitor, or pelleted, washed with PBS and resuspended in the lysis buffer.…”
Section: Bulk Rna-seq By Smart-seq2mentioning
confidence: 99%
“…There is no individual marker that specifically identifies bovine mammary stem cells [ 10 , 11 ]. Nevertheless, a limited collection of genes that are highly expressed in mouse and human mammary stem cells has been analyzed in extracts of bovine mammary parenchyma [ 8 , 24 ]. All of these markers were highly expressed in the rapamycin-treated glands, by 8–20% more than in their vehicle-treated counterparts ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Notable progress has been achieved in mouse mammary stem cell characterization since breakthrough studies were published, demonstrating reconstitution of a functional mammary gland by transplantation of a single or several stem cells into the de-epithelized mammary stroma [ 6 , 7 ]. Better separation from progenitors has been performed [ 8 ], new effectors, markers and subpopulations have been identified [Reviewed by [ 4 , 9 ]] and most importantly, unipotent luminal and basal stem cell populations with self-renewing potency have been identified in the postpartum mammary gland [ 1 ]. Together with their bipotent counterparts, these cells maintain the morphogenesis and homeostasis of the adult gland [ 2 ].…”
Section: Introductionmentioning
confidence: 99%